Crosstalk between Cell Adhesion Complexes in Regulation of Mechanotransduction - Zuidema, Alba; Wang, Wei; Sonnenberg, Arnoud (BioEssays, 2020)
Physical forces regulate numerous biological processes during development, physiology, and pathology. Forces between the external environment and intracellular actin cytoskeleton are primarily transmitted through integrin‐containing focal adhesions and cadherin‐containing adherens junctions. Crosstalk between these complexes is well established and modulates the mechanical landscape of the cell. However, integrins and cadherins constitute large families of adhesion receptors and form multiple complexes by interacting with different ligands, adaptor proteins, and cytoskeletal filaments. Recent findings indicate that integrin‐containing hemidesmosomes oppose force transduction and traction force generation by focal adhesions. The cytolinker plectin mediates this crosstalk by coupling intermediate filaments to the actin cytoskeleton. Similarly, cadherins in desmosomes might modulate force generation by adherens junctions. Moreover, mechanotransduction can be influenced by podosomes, clathrin lattices, and tetraspanin‐enriched microdomains. This review discusses mechanotransduction by multiple integrin‐ and cadherin‐based cell adhesion complexes, which together with the associated cytoskeleton form an integrated network that allows cells to sense, process, and respond to their physical environment. Cells assemble integrin‐ and cadherin‐containing adhesions that mediate interactions with the extracellular matrix and neighboring cells, respectively. In this review, the extensive crosstalk between distinct cell adhesions that regulates mechanotransduction is discussed.